Impact of Himalayan Singing Bowls Meditation Session on Mood and Heart Rate Variability - Panchal, Saharsh; Irani, Fariburz; Y Trivedi, Gunjan (International Journal of Psychotherapy Practice and Research, 2020)
Introduction Scientific evidence has established the benefits of meditation and sound vibrations on emotional and physiological health. Aim of the Study The study explored changes in mood and Heart Rate Variability (HRV) after HSB Sound Bath Meditation on healthy individuals. The objectives of the study were to understand if a 40-minute-long seated HSB Sound Bath Meditation results in changes (a) in mood measured via Positive And Negative Affect Scale (PANAS) and Abbreviated Profile of Mood States (POMS) Survey and (b) in physiological parameters, as measured by HRV. Methods The psychological parameters were measured with PANAS (N=77) and Abbreviated POMS, (N=17). The physiology was measured with HRV parameters such as Heart Rate (HR), Stress Index (SI) and Root Mean Square of Standard Deviation (RMSSD) using the EmWave Pro device (N=15). HRV data analysis was conducted with Kubios HRV Premium and analyzed using a paired T-Test. Results All the subjects after meditation showed improvement in Positive Affect (PA) and a reduction in Negative Affect (NA). The HRV parameters showed a trend showing overall relaxation with a significant reduction in HR, SI and an increase in RMSSD. Consistent with changes in positive, negative mood and HRV, all the participants showed a reduction in tension, anger, fatigue, depression and confusion and improvement in esteem related affect and vigor. Conclusion The findings show that seated HSB Sound Bath Meditation session has a positive impact on mood-related measures and physiology. Future work in this area could explore comparison with a control group and a longer study duration comprising multiple sessions.
Keywords: Himalayan Singing Bowls; Sound Bath Meditation; Heart Rate Variability (HRV); Mood; Sound Healing; Stress